2015
DOI: 10.2174/1568026615666150519102459
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening by Nuclear Magnetic Resonance (HTS by NMR) for the Identification of PPIs Antagonists

Abstract: In recent years the ever so complex field of drug discovery has embraced novel design strategies based on biophysical fragment screening (fragment-based drug design; FBDD) using nuclear magnetic resonance spectroscopy (NMR) and/or structure-guided approaches, most often using X-ray crystallography and computer modeling. Experience from recent years unveiled that these methods are more effective and less prone to artifacts compared to biochemical high-throughput screening (HTS) of large collection of compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 121 publications
5
53
0
Order By: Relevance
“…Here, instead of testing by NMR mixtures of possible of fragments and subsequently synthesize bi-dentate agents after pairs of ligands have been discovered (Becattini and Pellecchia, 2006; Chen et al, 2007; Petros et al, 2010; Shuker et al, 1996), we combine the fragments directly into a common scaffold and test by NMR the pre-assembled molecules in mixtures gathered in positional scanning fashion (Wu et al, 2015a; Wu et al, 2013). These studies led to the identification of the initial hit molecule compound 22 (Table 1) that was able to bind selectively to the EphA4-LBD in the mid-micromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…Here, instead of testing by NMR mixtures of possible of fragments and subsequently synthesize bi-dentate agents after pairs of ligands have been discovered (Becattini and Pellecchia, 2006; Chen et al, 2007; Petros et al, 2010; Shuker et al, 1996), we combine the fragments directly into a common scaffold and test by NMR the pre-assembled molecules in mixtures gathered in positional scanning fashion (Wu et al, 2015a; Wu et al, 2013). These studies led to the identification of the initial hit molecule compound 22 (Table 1) that was able to bind selectively to the EphA4-LBD in the mid-micromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…10−18 As an alternative to these strategies, we have recently proposed a novel approach, termed HTS by NMR, 19 in which the principles of positional scanning combinatorial chemistry 20−23 and fragment-based drug design are combined with protein-NMR spectroscopy 1 to iteratively identify and optimize antagonists from collections of >100,000 peptide mimetics. 19,24−26 The approach seems also particularly effective in the fragment-hit to lead optimization stages, when a positional scanning library is generated from an initial weak binder, perhaps common to a class of protein targets and/or previously identified from a FBDD campaign, 19,24,25 and tested by biophysical methods including not only NMR but also ITC. 27 Indeed, we recently demonstrated that testing a positional scanned library using the HTS by NMR approach revealed qualitatively a ranking that not only confirmed the known binding consensus motif for the BIR3 domain of the X-linked Inhibitor of Apoptosis Protein (XIAP), but also identified compounds that closely resembled a clinical agent (GDC-0152) 25 that targets it.…”
mentioning
confidence: 99%
“…19,24−26 The approach seems also particularly effective in the fragment-hit to lead optimization stages, when a positional scanning library is generated from an initial weak binder, perhaps common to a class of protein targets and/or previously identified from a FBDD campaign, 19,24,25 and tested by biophysical methods including not only NMR but also ITC. 27 Indeed, we recently demonstrated that testing a positional scanned library using the HTS by NMR approach revealed qualitatively a ranking that not only confirmed the known binding consensus motif for the BIR3 domain of the X-linked Inhibitor of Apoptosis Protein (XIAP), but also identified compounds that closely resembled a clinical agent (GDC-0152) 25 that targets it. Hence, to assess if this approach could be implemented to target metalloproteinases, we first derived a focused positional scanning (POS) combinatorial library of peptide mimetics (of approximately 100,000 compounds) where each element of the library contained the metal-chelating moiety hydroxamic acid at the C-terminal ( Figure 1A).…”
mentioning
confidence: 99%
“…Instead we refer to the many excellent reviews available on these topics. [12][13][14][15][16] The complex landscape of protein interactions…”
Section: Introductionmentioning
confidence: 99%